Tactics of Treatment of Severe Foot Injuries - Topvoldiev Saydillo Abduraxmonovich (Zien Journals, 2023)
Any, even minor, injury to the foot causes great discomfort, because every step gives off severe pain. At the same time, such injuries are one of the most common reasons for going to the emergency room. The human foot is a complex support and spring complex that carries the load of the whole body. In this article highlights of tactics of treatment of severe foot injuries
Keywords: modern medicine; foot injuries; treatment; modern tactics